15 Evaluating the novel bio-engineered stent in patients presenting with acute coronary syndrome. (27th November 2017) - Kalkman, D; Menown, I; Woudstra, P; Winter, RJ de
Abstract : Background: Patients presenting with acute coronary syndrome (ACS) are at increased risk of complications after percutaneous coronary intervention with stent placement compared to patients with stable coronary artery disease (CAD) treated in an elective setting. The novel COMBO stent (OrbusNeich, the Netherlands) is a bio-engineered drug eluting stent designed to promote vessel healing. It can potentially reduce this difference in clinical outcomes between elective and ACS-patients and prevent late stent thrombosis. Methods: The European, prospective, multicenter, 1000 patient REMEDEE Registry evaluates clinical outcomes after COMBO stent placement in an all-comers patient population. To evaluate the stents performance in ACS-patients we performed a subgroup analyses. The primary endpoint at 12 months is target lesion failure (TLF), a composite of cardiac death, target-vessel myocardial infarction and target lesion revascularisation. Clinical outcome in ACS and elective patients was evaluated. Cumulative events rates were estimated with the Kaplan-Meier method and compared with a log-rank test. Results: A total of 498 patient (49.9%) presented with acute coronary syndrome, 50.1% (n=500) were elective patient. TLF was 7.1% in ACS patients and 4.4% in elective patients, p=0.066. Stent thrombosis was observed in 0.5% of ACS patients and in 0.1% of elective patients, all within 9 days post stenting. Conclusions: The COMBO stent is a safe and efficient device for patients presenting with ACS. Low stent thrombosis rate and only early stent thrombosis were observed.